Law Enforcement of Corruption Cases Through a Participatory Society as an Effort to Protect Constitutional Rights - Diya Ul Akmal; Pipih Ludia Karsa; Syafrijal Mughni Madda (Faculty of Law, Universitas Lampung, 2021)
A participatory society can play an essential role in the prosecution of corruption cases. By providing information on alleged corruption, a participatory community can assist anti-corruption institutions so that corruption as an extraordinary crime can be eradicated as a means of enforcing people's constitutional rights. The authors attempt to perceive things by defending constitutional rights from a societal standpoint, a right of citizens who have had their rights violated by acts of corruption. The method used in this research is a normative legal method that refers to the norms in the laws and regulations, court decisions, and social society. The data used is secondary data obtained from various sources with appropriate and relevant topics so that it becomes chaotic in discussing related problems. The community's active role in uncovering corruption cases is part of the obligation to break the chain of corruption and fulfil citizens' rights to enforce the law. The amount of budget allocated for disclosing corruption cases is leading the government to protect citizens' constitutional rights from the threat of corruption. Although the handling is still considered unsuccessful because many cases have not been revealed, the efforts made deserve to be recognised.